2004
DOI: 10.1370/afm.71
|View full text |Cite
|
Sign up to set email alerts
|

Discussing Spirituality With Patients: A Rational and Ethical Approach

Abstract: BACKGROUND This study was undertaken to determine when patients feel that physician inquiry about spirituality or religious beliefs is appropriate, reasons why they want their physicians to know about their spiritual beliefs, and what they want physicians to do with this information. METHODSTrained research assistants administered a questionnaire to a convenience sample of consenting patients and accompanying adults in the waiting rooms of 4 family practice residency training sites and 1 private group practice… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
156
3
15

Year Published

2005
2005
2018
2018

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 239 publications
(177 citation statements)
references
References 26 publications
3
156
3
15
Order By: Relevance
“…That shows the existence of a gap between the desires of dialysis patients and the attitude of physicians. That result is in accordance with those of other international studies, in which 83% of the patients wanted their physicians to talk about their spirituality 39 and 94% of the patients wanted their physicians to ask about their religious beliefs when severely ill. 40 In conclusion, spirituality and religiosity play an important role for patients on dialysis. They are related to important points in the physician-patient relationship itself, quality of life, and facing the disease, and should be valued by the professionals caring for that type of patient.…”
Section: Methodssupporting
confidence: 92%
“…That shows the existence of a gap between the desires of dialysis patients and the attitude of physicians. That result is in accordance with those of other international studies, in which 83% of the patients wanted their physicians to talk about their spirituality 39 and 94% of the patients wanted their physicians to ask about their religious beliefs when severely ill. 40 In conclusion, spirituality and religiosity play an important role for patients on dialysis. They are related to important points in the physician-patient relationship itself, quality of life, and facing the disease, and should be valued by the professionals caring for that type of patient.…”
Section: Methodssupporting
confidence: 92%
“…A recent study among patients at a family medicine clinic found that 83% of the patients expressed preference to be asked about their spiritual beliefs by their physicians under three conditions: life-threatening illnesses, serious medical conditions, and loss of loved ones. 46 Although addressing the topic of religion in medical practice is laden with controversy, 47 it is evident that for religious/spiritual patients with advanced cancer, use of religious coping is likely to be common and important for their QOL. Moreover, our findings show that assessing religious coping (especially negative religious coping) might be important to understand patients who experience poorer QOL.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, evaluating the spiritual vision of patients alleviates their living problems. Therefore, a sound understanding of patients' spiritual beliefs is inseparable from patient care (50,51). Table 1 presents excerpts from some reviewed studies on the relationship between spirituality and health categorized according to mortality, coping and compliance, and recovery.…”
Section: Advantages Of Familiarity With Patients' Spiritual Visionmentioning
confidence: 99%